Materials Flow Analysis as a Tool to Improve Solid Waste Management: A Case of Ankara - Nesli Aydın (Doğal Afetler ve Çevre Dergisi)
The progress of recent civilisation and the associated growth in population worldwide has contributed considerably to the increase in the quantity of waste produced. The ever-increasing consumption of resources has resulted in high amounts of solid waste from domestic activities, which can pose significant threats to the environment and human health. Waste management and recycling activities have a complex and multifaceted mechanism that requires comprehensive and integrated approaches. In this study, the current status of municipal solid waste management in Ankara was identified and waste streams were investigated by using Materials Flow Analysis (Stan 2 software). It was aimed to analyse material flows by visualising the waste management system of Ankara. This study resulted that approximately 1.6 million tonnes of solid waste is collected per year (4500 tonnes per day) in the province. Almost 470 thousand tonnes of it is being used for methane production and more than 400 thousand tonnes of compost is being produced each year. The result of the model also points out that 286 thousand tonnes get accumulated in landfills each year. This reveals the possible requirement for a capacity investment of Mamak Landfill Area, which is already on the agenda of city authorities.